Prevalence and antimicrobial resistance in Streptococcus agalactiae isolated from raw milk in Pasuruan and Lumajang districts, East Java, Indonesia - DIAN AYU PERMATASARI; FAUZIAH ANGGRAENI; BUDIARTO BUDIARTO; DEWA KETUT MELES; IWAN SAHRIAL HAMID; YULIANA PUSPITASARI; MUSTOFA HELMI EFFENDI; ASWIN RAFIF KHAIRULLAH; DHANDY KOESOEMO WARDHANA; EMMANUEL NNABUIKE UGBO (Society for Indonesian Biodiversity, 2022)
Abstract. Permatasari DA, Anggraeni F, Budiarto, Meles DK, Hamid IS, Puspitasari Y, Effendi MH, Khairullah AR, Wardhana DK, Ugbo EN. 2022. Prevalence and antimicrobial resistance in Streptococcus agalactiae isolated from raw milk in Pasuruan and Lumajang districts, East Java, Indonesia. Biodiversitas 23: 5050-5055. Milk and dairy products are nutritionally important in the diet worldwide. The microbiological quality of raw milk is essential for the quality of the final dairy product. The presence of Streptococcus agalactiae is frequently associated with high somatic cell counts in milk and decreased milk yield. Streptococcus agalactiae infections have major consequences for public health. This study aimed to identify the prevalence and antimicrobial resistance of Streptococcus agalactiae isolated from raw milk in Pasuruan and Lumajang, East Java, Indonesia. Raw milk samples were collected from three sub-districts in Pasuruan (Tutur, Grati and Purwosari) and three sub-districts in Lumajang (Senduro, Karangbendo, and Tekung). California mastitis test (CMT) was performed to confirm the presence of somatic cells, S. agalactiae was identified using standard microbiological methods, and antibiotic resistance was determined by Kirby-Bauer disc diffusion method using Mueller-Hinton agar. Results showed that 89 (79.46%) out of 112 dairy cows were positive for CMT, which indicated the presence of mastitis. Bacteria isolation was performed on CMT-positive samples and four samples were showed the presence of S. agalactiae (4.49%). Based on the sensitivity test against various antibiotics, it was observed that S. agalactiae isolates were resistant to ampicillin (75%), and erythromycin (50%), and were sensitive to cefotaxime (100%), tetracycline (75%), and chloramphenicol (100%). This research reported that Streptococcus agalactiae organism is one bacterium that is implicated in mastitis infections. Therefore, monitoring the antibiotic susceptibility profiles of this organism is needed in veterinary medicine, in order to make an appropriate choice of drug for treatment, improve high cure rates and minimize the increase of drug resistance.